Gastric cancer in octogenarians. Is a curative surgery viable? - Apumayta, Elily D. (2023)
The objective was to evaluate the association between octogenarian age and the rate of postoperative morbidity and mortality and 5-year survival in older adults at the National Institute of Neoplastic Diseases (INEN) during the period 2000-2013. We developed an observational, retrospective, analytical, paired cohort study. It includes patients with gastric adenocarcinoma as diagnosis, treated by R0 D2 gastrectomy at INEN during the period 2000 to 2013. One group included all octogenarian patients who met the inclusion criteria (92) and the other group made up of non-octogenarian patients, aged between 50 to 70 years because it is the age peak for this pathology (276). In a 1:3 ratio, paired according to sex, tumor stage, and type of gastrectomy, which are the main factors that could influence survival in this population. Octogenarians had lower albumin level (p<0.002), lower preoperative hemoglobin (p<0.001) and higher ASA classification (p<0.001). 30 days mortality rate was higher in octogenarians but not statistically significant (4.1% vs 1.4%; p=0.099). The 5-year cumulative survival probability was 56% for octogenarians and 58% for non- octogenarians (p=0.763). Clinical stage ≥ III and postoperative complication grade ≥ 3 by Clavien Dindo scale were predictors of survival. In conclusion, octogenarians have a higher rate of postoperative morbidity, mainly for respiratory causes. Postoperative mortality and overall survival rates do not differ between octogenarians and non-octogenarians with stomach cancer treated by R0 D2 gastrectomy.